Determination of Sources of Atmospheric Pollutants in a Rural Background Area Using UMINIX-PMF Models Applied to Hourly Measurements of 64 VOCs Over 3 Years (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2014)
Currently, knowledge about the composition of volatile organic compounds (VOCs) in rural areas is still scarce compared to urban or industrial zones. Their determination in ambient air has become a relevant and important topic in recent years, mainly due to the participation of these compounds in atmospheric chemical reactions that lead to the formation of tropospheric ozone and other photochemical oxidants.The concentration of VOCs in ambient air is mainly the result of three processes: their emission, chemical reaction processes with ozone and OH radicals during the day and NO3 during the night, and mixing or dispersion processes. These can lead to large-scale transport of these pollutants, especially those with longer lifetimes.Valderejo, Álava (Spain), was declared a natural park in January 1992. The origin of the VOCs measured in the sampling area is both anthropogenic and biogenic. Among the anthropogenic sources of VOCs, the most relevant are vehicle emissions, solvent use, industry, and the use of natural gas, while vegetation represents the main biogenic source. Among the wide variety of biogenic emissions, isoprene and monoterpenes have been studied since they are clearly the most abundant in the area.Paraffins are the most abundant compounds detected in this environment, followed by olefins. More than 30 compounds show minimum and average values below the detection limit of the analytical equipment, which is characteristic of a rural background area. During the measurement period, concentrations of anthropogenic compounds have been decreasing due to the decline of industrial activity in the region. However, certain periods with slightly higher-than-usual concentrations reflect the influence of local traffic, human intervention, and atmospheric transport phenomena such as contaminated air masses.Receptor-source models use statistical procedures to identify and quantify pollution sources at a receptor location. The USEPA has developed three models: CMB (Chemical Mass Balance), UNMIX, and PMF (Positive Matrix Factorization). This type of receptor model has been used because it does not require prior knowledge of the profile of each source, needing only environmental measurement data and knowledge of source tracers to interpret the factors. These procedures allow, for example, the inference of the mixture of hydrocarbon sources impacting a given point, with the advantage of analyzing a multivariate data set using few components.In our case, the UNMIX 6.0 model was used to determine the possible number of factors (e.g., number of sources), and the PMF 3.0 (Positive Matrix Factorization) model with a larger number of species was applied to characterize the results obtained, identifying the different VOC sources affecting the area and quantifying their relative importance.